Binding of eIF3 in complex with eIF5 and eIF1 to the 40S ribosomal subunit is accompanied by dramatic structural changes - Zeman, Jakub; Itoh, Yuzuru; Kukačka, Zdeněk; Rosůlek, Michal; Kavan, Daniel; Kouba, Tomáš; Jansen, Myrte E; Mohammad, Mahabub P; Novák, Petr; Valášek, Leoš S (Nucleic acids research, 2019)
eIF3 is a large multiprotein complex serving as an essential scaffold promoting binding of other eIFs to the 40S subunit, where it coordinates their actions during translation initiation. Perhaps due to a high degree of flexibility of multiple eIF3 subunits, a high-resolution structure of free eIF3 from any organism has never been solved. Employing genetics and biochemistry, we previously built a 2D interaction map of all five yeast eIF3 subunits. Here we further improved the previously reported in vitro reconstitution protocol of yeast eIF3, which we cross-linked and trypsin-digested to determine its overall shape in 3D by advanced mass-spectrometry. The obtained cross-links support our 2D subunit interaction map and reveal that eIF3 is tightly packed with its WD40 and RRM domains exposed. This contrasts with reported cryo-EM structures depicting eIF3 as a molecular embracer of the 40S subunit. Since the binding of eIF1 and eIF5 further fortified the compact architecture of eIF3, we suggest that its initial contact with the 40S solvent-exposed side makes eIF3 to open up and wrap around the 40S head with its extended arms. In addition, we mapped the position of eIF5 to the region below the P- and E-sites of the 40S subunit.
Keywords: eukaryotický iniciační faktor 1; Saccharomyces cerevisiae Proteins; vazebná místa; eukaryotický iniciační faktor 5; Cryoelectron Microscopy; eukaryotický iniciační faktor 3; Saccharomyces cerevisiae; vazba proteinů; proteinové domény; Protein Domains; Ribosome Subunits, Small, Eukaryotic; Models, Molecular; Eukaryotic Initiation Factor-5; malé podjednotky ribozomu eukaryotické; molekulární modely; iniciace translace peptidového řetězce; Eukaryotic Initiation Factor-3; elektronová kryomikroskopie; Eukaryotic Initiation Factor-1; Saccharomyces cerevisiae - proteiny; Protein Binding; Peptide Chain Initiation, Translational; Binding Sites